Numerical Simulation of Magnetohydrodynamic Nanofluids Under the Influence of Shape Factor and Thermal Transport in a Porous Media Using CVFEM - Shah, Zahir; Babazadeh, Houman; Kumam, Poom; Shafee, Ahmad; Thounthong, Phatiphat (Frontiers in Physics, 2019)
In this article, migration of nanomaterial through a permeable domain was modeled numerically. Aluminum oxide was dispersed in to testing fluid which was selected water in current paper. Utilizing Darcy low for porous medium helps us to find simpler form of equations. Impact of shape factor and radiation on thermal conduct of nanoparticles inside a permeable space were investigated. Nanofluid inside a permeable space is taken under the magnetic force. CVFEM approach for simulation goal was applied. This approach provides advantages of two common CFD methods. Impacts of radiation, magnetic, buoyancy parameters on treatment of nanomaterial were demonstrated. Results prove that higher values of shape factor lead to stronger convection. By adding Lorentz forces, conduction becomes more sensible. Reverse relationship exist between Hartmann number and temperature gradient.